The Juridical Analysis of Registration of Business Permits through the Online Single Submission (OSS) System by Notaries - Khaidar, Naufal (TABELLIUS: Journal of Law, 2023)
This study aims to find out and analyze the registration of business licenses through the online system, Online single submissionsis a new licensing system based on PP No. 5 of 2021 where there is no notary authority in terms of business licensing in accordance with these regulations, but in practice there are many notaries who register business licenses for business actors. This research approach method includes sociological juridical research. Sociological juridical research is legal research using secondary data as initial data, which is then followed by primary data in the field or on the public, examining the effectiveness of a Ministerial Regulation and research that seeks to find relationships (correlations) between various symptoms or variables, as a data collection tool consisting of study of documents or library materials and interviews (questionnaire). The results of the research in this thesis entitled "Juridical Analysis of Registration of Business Permits Through the Online System (OSS)" namely, among others, Mandatory UUJN does not regulate the authority of a notary to provide services for handling all types of documents including the processing of business permits, but on the basis of the trust of the appearer who considers the notary having the ability and knowledge of all legal aspects and their derivatives, the appearer authorizes a notary to assist them in obtaining a business license for a business entity whose deed of establishment is drawn up by a notary. Reasons for the entrepreneur requesting the help of a notary to obtain a business license, OSS Basically, the appearers or entrepreneurs present before the notary do not have extensive legal knowledge or updates on new government regulations. especially when PP. No. 5 of 2021 for the promulgation of OSS, entrepreneurs are very confused about the registration of the intended business license, because since the birth of OSS, registration or application for business licenses has been carried out online (in the network) through the website www.oss.go.id, moreover, entrepreneurs have told the notary they have not received socialization on how to register a business license through the site so that entrepreneurs request the services of a notary.Keywords: Authority; Business; License; Registration; Submission.